Knowledge Transmission Channels from University to Industry : The Case of Korea - 성태경; Paul Sommers; 조현대; 이대희 (한국혁신학회, 2012)
The paper analyzes the transmission channels which university research influences industrial innovation in Korea. We categorize various knowledge transmission channels from university to industry into five groups: A(academic conferences), B(papers, reports, and patents), C(consulting, workshop, and networks), D(cooperative R&D and contract research),and E(joint venture, licenses, and spin-offs). We found that the important channels of knowledge flow between university and industry are more or less formal as well as more practical ones, notably Type D(cooperative R&D and contract research). However,informal channels such as Type C(consulting, workshop, and networks) and Type A(academic conferences) also may be influential on industrial innovation. Currently the Korean government, industry, and universities are likely to emphasize on Type E(joint venture,licenses, and spin-offs), which are reported as the least channel in importance in this study. In the future, it might be desirable to recognize the importance of other transmission channels such as academic papers, conferences, consulting, publications, and patents.